METHODS TO INCREASE STABILITY STEGANOSYSTEM FROM UNAUTHORIZED ACCESS - Чунарьова, А. В.; Потапенко, Є. О. (Science-based technologies, 2014)
We have made a systematic analysis of the currently existing methods for improving the stability of steganographic systems to various kinds of attacks to which the container may be subjected to steganographic channel transmission. All currently existing steganographic information security system can be divided into 3 groups, which include theoretically stable systems , ie those theoretical absolute reliability is mathematically proved in full. Robust steganographic system must implement three tier security model : Level 1 - steganography to hide confidential information; Level 2 - specific steganographic method , Level 3 - preliminary cryptographic encryption. In this paper, the systematization model stegosystem offender , as well as in accordance with this , the classification of types of attacks. As a result , are the most effective methods to protect steganographic data , and general recommendations on their use.